Estudio comparativo entre el laboratorio virtual y tradicional en estudiantes de la Carrera de Pedagogía de las Ciencias Experimentales: Matemáticas y la Física - Macas Villagrán, Cristhian Fernando (2024)
Education is constantly changing and adapting, always seeking to improve the teaching-learning process, where for certain subjects, mainly experimental ones and hard sciences such as mathematics and physics, tools are sought that facilitate this process in one way or another, this is how the use of laboratories in education emerged. Therefore, the general objective of this study was to carry out a comparative study between virtual and traditional laboratories in students of the Pedagogy of Experimental Sciences: Mathematics and Physics. The research has a quantitative approach, with a non-experimental design and a descriptive level, in addition to a type of cross-sectional, field and bibliographic study. The population on which we worked corresponds to students from the National University of Chimborazo of the Pedagogy of Experimental Sciences: Mathematics and Physics, choosing the sample after a non-probabilistic intentional sampling of students from the fifth to the eighth semester, to whom an evaluation instrument previously validated by experts was applied after obtaining a weighting of “excellent.” The results reflected that students usually feel satisfied with the practical application experience in virtual and traditional laboratories in general, but that they were more easily distracted in virtual laboratories in relation to traditional ones. Finally, both virtual and traditional laboratories can provide very important pedagogical support to this type of career and although both showed advantages and disadvantages, these are reduced or increased with the help of a teacher or technician in charge, but both encourage learning. to the students.